Caregiver's Interpersonal Communication Approach to The Elderly - Fatur Rahman (Winaya Inspirasi Nusantara Foundation, 2023)
Interpersonal communication is an interaction that occurs individually. Every elderly person living in a nursing home will be served by a caregiver every day. Therefore, it is very necessary for a caregiver to use it because it has an important role in assisting the elderly. This study aims to determine the interpersonal communication between caregivers and the elderly at Maghrifatullah Nursing Home, Deleng Pokhkisen District, Southeast Aceh Regency. The research methods used are observation, interview, and documentation. The subjects in this study were the head of the caregiver service section, the implementation of services, and the elderly. The results of this study indicate that the approach and obstacles to interpersonal communication between caregivers and the elderly consist of two forms, namely verbal communication and nonverbal communication. The process of interpersonal communication between caregivers and the elderly has been well achieved, where the communication approach that occurs is as a medium for storytelling, facial expressions (smiles), giving advice, and making activities or spiritual guidance programs and sports. While the communication barriers between caregivers and the elderly are physical, education, language, and personality.